The global syndemic of metabolic diseases in the young adult population: a consortium from the Global Burden of Disease 2000-2019. (25th January 2023) - Chew, N; Kannan, S; Chong, B; Chew, J; Lin, C X; Goh, R; Kong, G; Chin, Y H; Ng, C H; Foo, R; Chan, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: A large proportion of premature deaths are related to metabolic diseases in the young adult population. We examined the global trends and mortality of metabolic diseases using estimates from the Global Burden of Diseases, Injuries and Risk Factors Study (GBD) 2019 in individuals aged below 40 years. Methods: From 2000-2019, global estimates of prevalence, deaths, and disability-adjusted life years (DALYs) were described for metabolic diseases (type 2 diabetes mellitus [T2DM], hypertension, non-alcoholic fatty liver disease [NAFLD]). Global estimates were limited to mortality and DALYs for risk factors (hyperlipidemia and obesity). Subgroup analyses were performed based on sex, geographical regions and Socio-Demographic Index (SDI). Age-standardized prevalence, death, and DALYs were presented per 100, 000 population with 95% uncertainty intervals (UI). Findings: The prevalence for all metabolic diseases increased from 2000-2019, with the most pronounced increase in males and high SDI countries. In 2019, the highest age-standardised death rates were observed in hypertension (133·88 [121·25-155·73]; males, 160·13 [138·91-180·79]; females, 119·66 [102·33-136·86]), followed by obesity (62·59 [39·92-89·13]; males, 66·55 [39·76-97·21]; females, 58·14 [38·53-81·39]), hyperlipidemia (56·51 [41·83-73·62]; males, 67·33 [50·78-86·43]; females, 46·50 [32·70-62·38]), T2DM (18·49 [17·18-19·66]; males, 19·94 [18·50-21·32]; females, 17·30 [15·62-18·70]) and NAFLD (2·09 [1·61-2·60]; males, 2·38 [1·82-3·02]; females, 1·82 [1·41-2·27]). Similarly, obesity (1932·54 [1276·61-2639·74]) had the highest age-standardised DALYs, followed by hypertension (2885·57 [2580·75-3201·05]), hyperlipidemia (1207·15 [975·07-1461·11]), T2DM (801·55 [670·58-954·43]) and NAFLD (53·33 [40·73-68·29]). Mortality rates decreased over time in hyperlipidemia (-60%), hypertension (-47%), NAFLD (-31%) and T2DM (-20%), but not in obesity (107% increase). The highest metabolic-related mortality was observed in the Eastern Mediterranean and low SDI countries. Conclusion: The growing prevalence of metabolic diseases, increasing obesity-related mortality trends, and the sex-regional-socioeconomic disparities evident in young adulthood, present the concerning global burden of metabolic diseases now and in the years ahead. Figure 1A) Overall Deaths; 1B) DALYs Figure 2. Proportion of deaths